2017
DOI: 10.1016/j.rboe.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Can ethanol be used as an adjuvant to extended curettage in order to reduce the recurrence rate of aneurysmal bone cyst?

Abstract: ObjectiveThe best treatment of aneurysmal bone cyst (ABC) is still unclear. This study aimed to evaluate the usefulness of extended curettage and ethanol as an adjuvant to reduce local recurrence of ABCs.MethodsRetrospectively, 68 cases treated for primary and secondary ABCs caused by benign tumors from 2003 to 2013 were enrolled to a follow-up visit between one to ten years after the surgery. The treatment protocol was en-bloc resection, biopsy and curettage, extended curettage consisted of curettage, high-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Recently, the safety and effectiveness of anhydrous ethanol for adjuvant therapy after intraregional curettage of bone tumor has been reported. 1820 In a locally aggressive tumor, Oh et al 18 and Solooki et al 19 reported that anhydrous ethanol treatment after curettage reduced local recurrence rate in giant cell tumor and aneurysmal bone tumor, respectively. In benign tumors, Cha et al 20 reported the efficacy of anhydrous ethanol for the treatment of enchondroma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the safety and effectiveness of anhydrous ethanol for adjuvant therapy after intraregional curettage of bone tumor has been reported. 1820 In a locally aggressive tumor, Oh et al 18 and Solooki et al 19 reported that anhydrous ethanol treatment after curettage reduced local recurrence rate in giant cell tumor and aneurysmal bone tumor, respectively. In benign tumors, Cha et al 20 reported the efficacy of anhydrous ethanol for the treatment of enchondroma.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Moreover, the efficacy of ethanol to reduce recurrence rate after treatment of giant cell tumor, aneurysmal bone cyst, osteoid osteoma, skeletal metastasis, and other bone lesions has been described in the literature. [10,[19][20][21][22] To the best of our knowledge, the efficacy of ethanol as an adjuvant therapy in UBC lesions has not been described yet. In our study, we evaluated healing and recurrence rate of UBC lesions after ethanol usage as an adjuvant with curettage and bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Definite treatment of UBC lesions was conducted using our approach, called the combined four-step alcohol-using approach, consisted of extended curettage, high-speed burring, ethanol 96%, and electrocauterization of the lesion, consecutively. [10] Extended curettage was performed to remove all abnormal tissues. After using high-speed burr on the walls of the lesion, the defect was irrigated by normal saline.…”
Section: Methodsmentioning
confidence: 99%
“…ABC is a benign tumoral condition peaking at the first two decades of life[ 1 ]. Although different treatment options are available, commonly surgical treatment of ABCs including curettage with or without bone grafting in addition to different adjuvants or wide en-bloc resection of tumor is preferred[ 6 , 9 - 11 ]. Although the presented case was initially treated using curettage and bone grafting, recurrence was seen after 8 mo following the primary surgery.…”
Section: Discussionmentioning
confidence: 99%